Study of Supratentorial Tumours by Computed Tomography - Patil, Prashanth G; KM Nataraj; Saheb, Shaik Hussain (Asian Journal of Medical Radiological Research, 2020)
Background: Brain neoplasms may be classified by the location of supratentorial, infratentorial and midline tumours. Of the supratentorial neoplasms, meningiomas are the most frequent extra-axial neoplasms. CT has become the most important diagnostic procedure in evaluating patients suspected of harboring an intracranial tumor. It is still considered the basic radiologic study since it gives specific information for the management of brain tumours and is minimally invasive. The purpose of this study was to assess the distribution, features, localization and extent of supratentorial neoplasms. Subjects and Methods: Fifty cases with symptoms of intracranial pathology and on CT found to have supratentorial tumours were studied. Results: The CT patterns of 50 supratentorial tumours were reviewed, out of which 30 cases i.e. 60%, were found to be intra- axial and 20 i.e. 40% extra-axial tumours. GBM formed the major group of the intra axial tumours i.e. 18 %, and meningiomas formed the major extra-axial tumours forming 26%. Conclusion: CT proves to be a valuable modality of imaging in evaluating the distribution, features, localizing and assessing the extent of various intra and extra-axial tumours in the supratentorial region.